Determination of parameters affecting the use of complementary and alternative medicine in cancer patients and detection of prevalence of use - MAYADAĞLI, ALPASLAN; Mayadagli, Alpaslan; Aksu, Atinc; Goksel, Fatih; Gocen, Erkan; KARAHACIOĞLU, ERAY; Gumus, Mahmut; Pak, Yucel (My University, 2011)
This study was conducted to find out the frequency of complementary and alternative medicine (CAM) use that could lead to troubles in patient health and in applied standard therapy protocols when used improperly, which method is used, the reasons for use and from which resources the information about this topic were obtained. A questionnaire consisting of 28 questions was applied to 195 patients with cancer diagnosis by a face-to-face interview. The obtained data were assessed with SPSS 11.5 program. Out of 195 cancer patients, 100 (51.3%) were using CAM and 48.7% (n=95) were not. The most commonly used agent was nettle (72%). This was followed by herbal teas (21%), grape molasses (20%) and black seed (20%). The frequency of CAM use was found higher in those under age 50, in literate people, in those working during the diagnosis stage and having disease at the later stage. While CAM was commonly recommended by friends and relatives of the patients (73%), this ratio was only 5% for health professionals. While 51.3% of all patients were gathering information about CAM, 75% of those actually using CAM gathered information about it. Whilst information was gathered mostly from the relatives of patients and tamperers (47%), it can be gathered from physicians only with a ratio of 10%. Cancer patients use CAM and they gather information mainly from unreliable sources rather than physicians. Although the primary information source should be physicians, the ratio for this was very low (10%). We suggest that physicians should spend more time in gathering correct information and sharing them with their patients for a better guidance.